Consumers' preferences for bioplastic products: A discrete choice experiment with a focus on purchase drivers. (1st January 2022) - Notaro, Sandra; Lovera, Elisabetta; Paletto, Alessandro
Abstract: The excessive use of conventional plastics is causing some environmental problems, such as carbon dioxide emissions and plastics pollution. Bio-based plastics can potentially be beneficial for the environment by replacing conventional fossil-derived raw materials with renewable more sustainable alternatives. Despite expected production increase, the bioplastic market is currently limited because of low availability and lack of information, high prices and poor marketing activities. With the application of a Discrete Choice Experiment, this study was able to determine consumers' preferences and willingness to pay for some environmental characteristics related to a jacket and a pack of disposable cups both made of bio-based plastics, using a sample of 1115 Italian consumers. The analysis revealed that most consumers are willing to pay more for a bioplastic jacket and for disposable cups made of bioplastics than the corresponding fossil-based plastic products. Consumers prefer bioplastic products made from 100% wood-based plastics, biodegradable in less than six months and with information on climate protection. By comparing the two products, results showed that consumers are subject to price sensitivity, as their premium prices are proportionately higher for the less expensive bioplastic product. Purchase intentions, subjective norm, control on perceived costs, climate impact together with gender, age, income and high school diploma have been found to be influential purchase drivers. These results can represent a starting point for the development of strategies for market promotion and penetration and to increase bioplastics knowledge, availability and market shares. Highlights: Bio-based polymers market is globally a niche market Consumers are willing to pay a premium price for bioplastic products Premium prices are proportionately lower for more expensive bioplastic products Short biodegradability, climate protection, 100% wood-based are preferred features